2022
DOI: 10.3390/polym14163342
|View full text |Cite
|
Sign up to set email alerts
|

The Incorporation of Low-Molecular Weight Poly(Mannitol Sebacate)s on PLA Electrospun Fibers: Effects on the Mechanical Properties and Surface Chemistry

Abstract: We offer a report on the synthesis of low-molecular weight biobased poly(mannitol sebacate) (PMS) and its functionalization with acrylate groups (PMSAc). These synthesized polyesters were blended at a low level (10 wt%) with poly (lactic acid) PLA to prepare aligned fibers by electrospinning, coupled with a rotatory collector. The obtained fibers were extensively studied by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), differential scanning calorimetry (DSC), and wide-angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The synthesis of a PMS polyester from D-mannitol and sebacic acid and its subsequent functionalization with acrylate groups was successfully performed previously [ 34 ]. These polymers were incorporated into poly(lactic acid) to create functionalized fibers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of a PMS polyester from D-mannitol and sebacic acid and its subsequent functionalization with acrylate groups was successfully performed previously [ 34 ]. These polymers were incorporated into poly(lactic acid) to create functionalized fibers.…”
Section: Resultsmentioning
confidence: 99%
“…1 H NMR (400 MHz, CDCl 3 , ppm): δ = 8.52 (s, 1H; =CH thiazole), 6.02 (m, 1H; =CH), 5.49 (m, 1H; =CH), 4.22 (t, J = 6.5 Hz, 2H; OCH 2 ), 3.06 (t, J = 6.5 Hz, 2H; CH 2 ), 2.33 (s, 3H; CH 3 thiazole), 1.84 (dd, J = 1.2, 1.5 Hz, 3H; CH 3 ); 13 C NMR (400 MHz, CDCl 3 , ppm): δ = 166.9 (C=O), 149.9 and 149.7 (NCs), 135.9 (–C=CH 2 ), 126.8, 125.8 (=CH 2 s and C=C–S), 64.1, 25.7, 18.3, 14.7. Poly(mannitol sebacate) (PMS) (Mn and Ð obtained by SEC were 2480 g/mol and 1.22, respectively) and PMS-Ac (~80% of functionalization) were also synthesized according to previously published methods [ 34 ]. Briefly, PMS was synthesized from SA and D -mannitol in bulk at 150 °C in a molar ratio SA/MA of 1/1.1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing the mechanical behavior of blends with similar works, it becomes apparent that blending these bioelastomers with their families is a more effective method for adjusting mechanical behavior without compromising other advantages. 17,25,26,33…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Nonetheless, it should be noted that an increase in the percentage of polylactic acid has led to the observation of inflammation in the rat's body. 25,26 Moreover, it has been observed that this particular family of bioelastomers can be combined with minerals, vitamins, and drugs to create suitable composites for drug delivery and tissue engineering applications. 24,[27][28][29][30] Through the blending of poly (glycerol sebacate) with polycaprolactone, it has been demonstrated that it is possible to maintain biocompatibility at a level comparable to pure poly (glycerol sebacate) while also achieving a wide range of mechanical properties.…”
Section: Introductionmentioning
confidence: 99%